If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 24 = y + -12 Reorder the terms: 24 + x = y + -12 Reorder the terms: 24 + x = -12 + y Solving 24 + x = -12 + y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + x = -12 + -24 + y Combine like terms: 24 + -24 = 0 0 + x = -12 + -24 + y x = -12 + -24 + y Combine like terms: -12 + -24 = -36 x = -36 + y Simplifying x = -36 + y
| 21+5(x-4)=4(x+5) | | x^3+14x^2+61x+84=(x+3) | | x+24=y+12 | | 3x-12=138 | | 8x-8=12x+24 | | 10-n=15-5 | | 9-3r=r-1 | | 15=9-2x | | 20+4m=1m-10 | | 12+7(3q-5)-2(q+8)+6= | | 25-4x=17 | | (x+1)(-x^2+5x-6)=0 | | 2x+3y=33 | | x+24=y*5 | | y-3+4=11 | | x+24=y | | 3x^4+30x^2-27=0 | | 24x^2=113x+80 | | 5.2(x-3)+8x= | | 20x+11x-42=0 | | 6x+21=8x+9 | | 3/5x-1/3x=4/9x+1 | | x-1=2+x | | -7y^2+wy-x=0 | | x=-3y-8 | | x^2-5x-4x^2=-8x | | 10=2d+3 | | x^2-5-4x^2=-8x | | 5x^2-8x=3x^2-6x | | -3x-x^2=-4 | | 4x^2+4x=x^2-8x | | 7-y/5=3/4 |